Digital Asset Management: A Lowdown on Intricacies of Digital Rights and Permissions - Chimakurthi, Venkata Naga Satya Surendra (Global Disclosure of Economics and Business, 2020)
The adaptability of digital asset management has prevailed enormous businesses and individuals who desire to manage information effectively. The criteria of this paper will revolve around the in-depth intricacies of digital asset management, its functions, significance, and categories of DAM. The introduction of digital rights and permissions aligned with highlighted copyright permission. Initializing from manual asset management and proceeding towards digital asset management, media asset management, and finalizing at massive content management, these terms seem to be striving to explain a unified thing. However, each domain of asset management has separate aspects of managing information. Every organization will opt for its criteria of approach for managing the assets that rely upon the environmental, current cultural, and financial state of the company.